The Problems Detected in Mushroom Cultivation in Ankara - Mürüvvet Ulusoy Deniz; Şule Tütüncü; Erkan Eren (Turkish Journal of Agriculture: Food Science and Technology)
Development of the cultivated mushroom farming which began to be produced in the 1960s in Turkey, has been more faster in the Mediterranean region than other regions. The development of mushroom cultivation has began to seen Marmara and İç Anadolu regions in recent years. The mushroom production which is very important for human health and nutrition, has been changing year to year (sometimes increase, sometimes decrease) in the province of Ankara. The first private mushrrom cultivation company had been established in1963. Up to date, the number of private enterprises has changed over the years in Ankara. This study was carried out by doing a survey with an active 12 enterprises which the annual production capacity of 10-600 ton. The enterprises were visited and problems were determined during the cultivation. As a result of the study, It was observed that there are problems in production and marketing phases and with surface soil material